Pengaruh latihan napas dalam terhadap perubahan tekanan darah pada penderita hipertensi esensial Di Puskesmas Putri Ayu Kota Jambi - Yani, Fithri (Riset Informasi Kesehatan; Vol 6 No 2 (2017): Riset Informasi KesehatanDO - 10.30644/rik.v6i2.88, 2017)
Abstract   Background : Based on health surveys, 30% of Indonesians are hypertension. Hypertension is a risk factor for third-leading cause of death after stroke and tuberculosis i.e. 67% of the population death at all ages. Total patients with essential hypertension at the public health center Putri Ayu Jambi city year 2016 as many as 2490 patients. This study aimed to determine is there any effect of provision of nursing interventions in the form of deep breathing relaxation to changes in blood pressure in patients with essential hypertension at the public health center Putri Ayu Jambi city. Method :This study used one group pre-post test design method; it used purposive sampling technique, with total samples as many as 30 respondents from total population as many as 378 patients. Instruments are Blood pressure measurement results, data analyzed as univariate and bivariate by using paired t-test analysis. Results :The findings indicated that p-value Systole blood pressure p-value = 0.000 and diastole p-value = 0.006, so it concluded that there is significant effect to Changes in blood pressure in patients with essential hypertension Before and after being given deep breathing exercises at the public health center Putri Ayu Jambi city. Conclusion :It is expected that health officer to increase the Giving nursing care and can provide knowledge about deep breathing exercises so that people with essential hypertension can control blood pressure independently at home.